Candidate Reference Measurement Procedure for the Quantification of Total Serum Cortisol with LC-MS/MS. (6th January 2020) - Hawley, James M; Owen, Laura J; MacKenzie, Finlay; Mussell, Chris; Cowen, Simon; Keevil, Brian G
Abstract: BACKGROUND: Accurate measurement of serum cortisol is required to diagnose and treat adrenal disorders. Although certified reference materials (CRMs) are available to standardize cortisol measurements, External Quality Assessment (EQA) schemes still demonstrate a wide dispersion of results. We present a serum cortisol candidate reference measurement procedure that, through analysis of a Joint Committee for Traceability in Laboratory Medicine–listed panel of higher-order CRMs, provides metrologically traceable results. METHOD: Isotope-labeled internal standard was added to samples before supported liquid extraction. Extracts were analyzed with LC-MS/MS in positive electrospray ionization mode. Multiple reaction monitoring was used to detect cortisol and its corresponding internal standard transitions. We measured samples in triplicate over 3 days and calculated the mean result. RESULTS: Mean intra- and interassay imprecision were 1.3% and 1.5%, respectively, for concentrations of 154, 510, and 769 nmol/L. Ionization efficiency studies and structural analog analysis proved the method to be robust against interferences. Through analysis of 34 CRMs (83–764 nmol/L), expanded measurement uncertainty was calculated to be 5% (95% CI). The mean bias between the measured and target CRM concentrations was statistically insignificant at −0.08%. CONCLUSIONS: The accuracy and low measurement uncertainty of this method qualify it as a CRM procedure. Metrological traceability has been achieved through the analysis of higher-order CRMs. This method could be used to underpin serum cortisol EQA schemes to provide samples with a traceable target value, enabling participating laboratories to determine the accuracy and measurement uncertainty of their assays.